Integration of Internet of Things and Digital Accounting Systems for Marine Resources Monitoring - Renaldo, Nicholas (Interconnection: An Economic Perspective Horizon, 2024)
This study explores the integration of Internet of Things (IoT) technologies and digital accounting systems in marine resource management, providing insights into how these technologies can improve operational efficiency, enhance sustainability, and optimize resource usage. The research follows a case study design with qualitative approach, which allows for an in-depth examination of the integration of IoT and digital accounting in specific marine industries, such as fisheries, aquaculture, and maritime logistics. The findings reveal that IoT is already being used for real-time environmental monitoring in industries like fisheries, aquaculture, and maritime transport, while digital accounting systems are primarily employed for financial and operational management. However, the integration of IoT data with digital accounting is still in its early stages, and challenges such as technical barriers, data overload, and system compatibility must be addressed to fully realize the potential of these technologies.